Are lower levels of red blood cell transfusion more cost-effective than liberal levels after cardiac surgery? Findings from the TITRe2 randomised controlled trial. Issue 8 (1st August 2016) - Stokes, E A; Wordsworth, S; Bargo, D; Pike, K; Rogers, C A; Brierley, R C M; Angelini, G D; Murphy, G J; Reeves, B C
Abstract : Objective: To assess the incremental cost and cost-effectiveness of a restrictive versus a liberal red blood cell transfusion threshold after cardiac surgery. Design: A within-trial cost-effectiveness analysis with a 3-month time horizon, based on a multicentre superiority randomised controlled trial from the perspective of the National Health Service (NHS) and personal social services in the UK. Setting: 17 specialist cardiac surgery centres in UK NHS hospitals. Participants: 2003 patients aged >16 years undergoing non-emergency cardiac surgery with a postoperative haemoglobin of <9 g/dL. Interventions: Restrictive (transfuse if haemoglobin <7.5 g/dL) or liberal (transfuse if haemoglobin <9 g/dL) threshold during hospitalisation after surgery. Main outcome measures: Health-related quality of life measured using the EQ-5D-3L to calculate quality-adjusted life years (QALYs). Results: The total costs from surgery up to 3 months were £17 945 and £18 127 in the restrictive and liberal groups (mean difference is −£182, 95% CI −£1108 to £744). The cost difference was largely attributable to the difference in the cost of red blood cells. Mean QALYs to 3 months were 0.18 in both groups (restrictive minus liberal difference is 0.0004, 95% CI −0.0037 to 0.0045). The point estimate for the base-case cost-effectiveness analysis suggested that the restrictive group was slightly more effective and slightly less costly than the liberal group and, therefore, cost-effective. However, there is great uncertainty around these results partly due to the negligible differences in QALYs gained. Conclusions: We conclude that there is no clear difference in the cost-effectiveness of restrictive and liberal thresholds for red blood cell transfusion after cardiac surgery. Trial registration number: ISRCTN70923932; Results.